A sense of direction: spatial boundaries in a cognitive, cultural, and deep time perspective. (3rd April 2022) - Løvschal, Mette; Skewes, Joshua Charles
ABSTRACT: This brief note points toward new potentials that lie at the interface between research on landscape archaeology and cognitive science. Recent advances in the cognitive and neural sciences have sharpened our understanding of spatial cognition, by providing new explanations for how the brain reduces the dimensionality of complex topography and geography for effective navigation. This research suggests that space is represented in grid-like structures in the brain, and that grid-like forms are a basic ingredient of spatial processing. At the same time, recent archaeological research shows that the organization of larger-scale space into linear forms, and in particular grid-like landscapes, is a relatively recent social invention, which suggests that these forms are historically and culturally contingent. Taken together, this research raises the question of how the dimensionality-reducing function of grid-like processing in the brain is related to higher-level conceptual and imaginative processing of space needed to plan and negotiate large-scale landscape structures. This brief note motivates this question and argues for further exploration of the relationships between biological, cognitive, and cultural processes related to space and its conceptualization between these fields of research.